Influence of goal orientation on players' performance with special reference to Sri Lanka national team sports - Perera, H. P. N.; Jusoh, M.; Azam, S. M. F.; Sudasinghe, S. R. S. N. (International Journal of Human Movement and Sports Sciences, 2019)
The purpose of the present research was to study the relationship between goal orientation and performance in team sports players. The Task and Ego Orientation in Sport Questionnaire (TEOSQ) was used for the assessment of goals. The observed variable of the study was perceived performance and was measured through a likert scale questionnaire, which had been adopted from literature. Subjective performances of the players were considered. Data was collected from Sri Lankan national team players who are engaged in team sports of football, basketball, Elle, volleyball, Hockey, Kabaddi, Netball, Rugby and Throw ball. The study population was 308 national team players and the universal sampling technique was used. Data were analyzed using SPSS and structural equation modeling with AMOS. The study results reveal that there is a significant association between goal orientation and performance of the players while a significant relationship exists between task orientation and performance. A moderate level of association was derived from ego orientation which in turn leads to performance.